2020
DOI: 10.32360/acmar.v53i1.41888
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição Espaçotemporal Dos Parâmetros Abióticos E Bióticos Em Um Estuário Amazônico (Brasil)

Abstract: O objetivo deste trabalho foi avaliar a distribuição dos parâmetros abióticos (temperatura, salinidade, pH, oxigênio dissolvido, taxa de saturação de oxigênio dissolvido, material em suspensão, N-amoniacal, nitrito, nitrato, fosfato e silicato) e biótico (clorofila a) em relação aos períodos climáticos da região Amazônica, no estuário Guajará-Mirim, localizado em Vigia, no Pará. As coletas de água para análises dos parâmetros abióticos e biótico ocorreram nos meses de setembro e novembro de 2011 e janeiro, mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(21 reference statements)
1
2
0
2
Order By: Relevance
“…Seasonal and spatial variation of salinity was very significant (p < 0.05), as expected, since they were probably influenced by rainfall regimes in the regions, considering that the higher the precipitation, the lower the environmental salinity rates tend to be (Santos et al, 2020). It is important to emphasize that the salinity at the sample points (p < 0.05 ANOVA oneway) also varied in the region of São Luís and São José de Ribamar, where the tide-control structures may influence not only the organisms but also some abiotic parameters.…”
Section: Discussionsupporting
confidence: 77%
“…Seasonal and spatial variation of salinity was very significant (p < 0.05), as expected, since they were probably influenced by rainfall regimes in the regions, considering that the higher the precipitation, the lower the environmental salinity rates tend to be (Santos et al, 2020). It is important to emphasize that the salinity at the sample points (p < 0.05 ANOVA oneway) also varied in the region of São Luís and São José de Ribamar, where the tide-control structures may influence not only the organisms but also some abiotic parameters.…”
Section: Discussionsupporting
confidence: 77%
“…O n-amoniacal foi a espécie predominante entre os compostos nitrogenados, que apresentou concentrações estáveis e distribuiu-se linearmente em todo o estuário. Sua variação longitudinal pode estar relacionada ao processo de nitrificação, com o n-amoniacal resultante da conversão do nitrato ou nitrito, tornando as concentrações desta forma relativamente mais baixas, Santos et al, (2020), corrobora em seus estudos o comportamento semelhante na distribuição espaçotemporal dos parâmetros abióticos e bióticos em um estuário Amazônico (Brasil). De acordo com Monteiro (2015) este processo pode ter sido controlado pelo aporte dos sedimentos do fundo, uma vez que ao longo das margens do furo que ficam do lado da comunidade Beira Mar temse as menores profundidades.…”
Section: Discussionunclassified
“…In the present work, the influence observed in the distribution of temperature values was related to the collection time, as shown in Figure 3b, at 4:40 pm the highest temperature value was observed (Table 1). Effects of the hydrodynamics of Guamá river estuary on the dispersion of organic load in Tucunduba Igarapé, Belém, Pará (Brazil) State Santos et al (2020) observed small variations in temperature and pH between tides in an estuarine area in the State of Pará (Guajará-Mirim Estuary). The small variation in pH (Figure 3a) is related to the existing buffering effect in aquatic ecosystems, which is verified by the slightly acidic values found in the present study.…”
Section: /10mentioning
confidence: 99%
“…Despite the acidic values, it was observed that the pH was within the acceptable value for aquatic environments described by Hasan et al (2022): pH less than 7 but greater than 8.5 is not ideal for productivity, and less than 4 is considered harmful to aquatic life. Waters from the estuaries of the State of Pará has acidic pH values and is related to the local geology (Oliveira et al, 2022;Santos et al, 2020;Varela et al, 2020).…”
Section: /10mentioning
confidence: 99%